Awakening Anti-Bullying Awareness through the "Find Friends" Game in the Boarding School Environment - Noviyanti, Tausyiah Rohmah; Riska Oktaviana; Aprillia Nurhayati; Asma Nadia; Eva Ardiana; Ira Nurmala (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: Indonesia ranks 4th in violence cases and 2nd in bullying cases worldwide, following Japan. Bullying, increasingly common in school environments, has become a public health issue. Alarmingly, bullying incidents have infiltrated even morally-focused educational settings like Islamic boarding schools. This necessitates effective interventions to raise awareness and curb bullying. The interactive edutainment game "Find Friends," designed for group play, holds promise as a tool to build awareness and encourage positive behavior change in a fun, engaging manner. Objectives: This study aims to analyze the effectiveness of the "Find Friends" game in increasing anti-bullying awareness among students at an Islamic boarding school and promoting positive behavioral changes. Methods: A pre-experimental one-group pretest-posttest design was used in this intervention study, conducted in August 2024 at Pondok Pesantren X, Sukoharjo District. All 31 junior high school students participated as respondents. Data were collected through a checklist assessment and analyzed using the Wilcoxon test. Results: The findings showed no statistically significant difference in students’ knowledge and attitudes toward bullying behavior, although there was a 4.8% increase in the average knowledge scores from pre-test to post-test on anti-bullying awareness. Conclusion: Although "Find Friends" demonstrated potential in boosting anti-bullying awareness, students' knowledge levels on bullying behavior did not significantly change in this study. Factors such as pre-existing knowledge from school may have influenced the results. Future studies with larger samples and extended intervention periods are recommended to explore the deeper impact of the game and to refine its methods for enhanced effectiveness.